(untitled) (Journal of Advanced Research in Social Sciences, 2024)
Deeply ingrained in the fabric of Chinese society, calligraphy originated as an ancient art form and is known as the chief of all traditional arts in China. In the current artistic context of the People’s Republic of China (PRC), calligraphy has merged with contemporary art forms to reflect the dynamic changes and realities of the country. Addressing gaps in academic literature focusing on China’s soft power and cultural diplomacy, this paper focuses on cultural relations to develop a people-centered pathway that flows “organically” and enables the understanding of current-day China. Inspired by Anne Marie-Slaughter’s conceptualization of a “web” of networks, this paper employs a case study analysis of specific contemporary artworks by Chinese contemporary artist Qiu Zhijie. Indeed, this paper finds that Qiu’s maps reflect nuances of contemporary Chinese society, showcasing the intricate relationship between calligraphy, contemporary Chinese art forms, and Chinese culture and society. Further, due to the unique combination of Chinese characters and English text, woven together through cartography and Chinese calligraphy, Qiu’s maps provide international audiences with basic tools for understanding cross-cultural nuances and contemporary realities. In the context of international relations, Qiu’s maps may act as a medium for improving the international community’s understanding of current-day China.